2016
DOI: 10.1093/nutrit/nuw019
|View full text |Cite
|
Sign up to set email alerts
|

Normal-weight obesity syndrome: diagnosis, prevalence, and clinical implications

Abstract: The growing concern about the impact of overweight on health has led to studies that shed light on types of obesity other than the classic model based on body mass index. Normal-weight obesity syndrome is characterized by excess body fat in individuals with adequate body mass index (18.5-24.9 kg/m(2)). This condition increases the risk of cardiovascular morbidity and mortality and other conditions associated with chronic diseases, such as insulin resistance, hypertension, and dyslipidemia. The aims of this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 40 publications
2
123
0
6
Order By: Relevance
“…Exercise interventions such as high-intensity interval training and resistance training have been shown to be especially effective at reducing abdominal fat and increasing leg LM, while also being feasible and enjoyable in obese populations [48,49]. Although current results are limited to overweight and obese individuals, segmental evaluation of body composition could also prove to be insightful in identifying at-risk normal and underweight individuals who often go undetected due to their normal weight status [50]. In conclusion, LM and FM, specifically trunk LM, leg LM, trunk FM, and VAT, were significantly associated with metabolic rate and substrate utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise interventions such as high-intensity interval training and resistance training have been shown to be especially effective at reducing abdominal fat and increasing leg LM, while also being feasible and enjoyable in obese populations [48,49]. Although current results are limited to overweight and obese individuals, segmental evaluation of body composition could also prove to be insightful in identifying at-risk normal and underweight individuals who often go undetected due to their normal weight status [50]. In conclusion, LM and FM, specifically trunk LM, leg LM, trunk FM, and VAT, were significantly associated with metabolic rate and substrate utilization.…”
Section: Discussionmentioning
confidence: 99%
“…This group is defined by a normal body weight and BMI, but an elevated body fat percentage, comparable to that of obese individuals. There are already studies showing similar associations of normal weight obesity with metabolic syndrome and insulin resistance and obesity related co-morbidities (167)(168)(169). Less is known about the impact of normal weight obesity on immune cells and the resulting risk for cancer burden.…”
Section: Effects Of Systemic Obesity On Human Nk Cellsmentioning
confidence: 99%
“…Several recent studies have uncovered metabolic dysregulation in people classified with NWO [6], even among adolescents [9]. Confirming these results, our study suggests that NWO boys and girls show significantly higher levels for WC, triglycerides, systolic blood pressure, and cardiometabolic risk score than their NWL peers, and a lower level of HDL-C. On the basis of published studies, we can speculate that youth with NWO show altered levels of proinflammatory cytokines, which may contribute to an increased risk of developing cardiometabolic disorders [6]. Similarly, Olafsdottir et al [9] reported that metabolic risk was considerably higher among NWO adolescents than their NWL peers, with high WC being more prevalent in the former.…”
Section: Discussionmentioning
confidence: 99%
“…Two research groups are involved in the project: (a) Center of Studies in Physical Activity Measurements, School of Medicine and Health Sciences, University of Rosario, and (b) District Education Secretary, Bogotá, DC. All participants were of low-middle socioeconomic status (SES; 1-3 in a scale of 1-6 defined by the Colombian government) and were enrolled in 20 public elementary and high schools (i.e., grades [5][6][7][8][9][10][11]. The participants answered a questionnaire (paper-and-pencil format) containing information on socioeconomic, demographic, and behavioral variables (i.e., alcohol intake, diet, tobacco) during the 2014-2015 school year.…”
Section: Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation